Cultural Values in Improving the Quality of Madrasah Education in Indonesia - Sri Mulyati; Muhammad Al-Mighwar (STIT Attaqwa, 2023)
There is a need for reform in a national education order that is in line with developing demands. Therefore, in the world of education , improving the quality of education has a very big role. Improving the quality of an educational institution means improving the quality of students from that educational institution to be better and highly competitive with various outstanding achievements. The cultural values in improving the quality of madrasas are (1) discipline values , (2) responsibility values, (3) togetherness values, (4) openness values, (5) honesty values, (5) ways of respecting other individuals, (6) social values, (7) values of unity and unity. Implementation starts from implementing a culture of discipline and also a culture of hard work which is instilled and carried out by all parties in the madrasa.